An Analysis of Students’ Ability in Writing Recount Text of The Third Semester Students of English Department in Nommensen HKBP University, Medan - Simarmata, Rina Octavia; Silitonga, Harpen; Simamora, Suhendra (Innovative: Journal Of Social Science Research, 2024)
The aim of the research was to find out the ability in writing recount text of the Third Semester Students of English Department in Nommensen HKBP University, Medan”. The method of this research was descriptive quantitative research. Writing test was used as the instrument of collecting data. the subject of this research was group B of the Third Semester Students of English Department in Nommensen HKBP University, Medan. The result in this test was good and the mean score was (78,37). The results of research in writing vocabulary in recount texts show that the students’ ability is good to average, the result shows that 9 students (45%) have excellent to very good ability, 7 students (35%) have good to average ability, and 4 students (20%) have fair to poor ability. Students' language use ability is good to average, the results show that 6 students (30%) have excellent to very good ability, 12 students (60%) have good to average ability, and 2 students (10%) has fair to poor ability, this showed the students of the Third Semester Students of English Department were able to writing recount text